058 Perceived barriers and facilitators towards an injury prevention program in professional male ice hockey teams among players and staff members. (3rd March 2020) - Brunner, Romana; Bizzini, Mario; Maffiuletti, Nicola; Niedermann, Karin
Abstract : Background: Lower extremity injury prevention programs are effective in team sport athletes. Objective: This study identifies barriers to and facilitators for an injury prevention program in professional male ice hockey teams among players and staff members. Design: Cross-sectional survey. Setting: Professional male ice hockey teams. Participants: Eight Swiss National League A (NLA) teams and their staff members were invited to participate in the study and voluntarily completed the questionnaire. Inclusion criteria were the ability to understand German or English and signed informed consent. Six teams completed the questionnaire (148 players and 11 staff members). Main outcome measurements: Frequency of ratings related to knowledge, attitude, adherence and habits were analysed. Binary logistic regression analysis was applied to predict a relationship between players' characteristics and positive attitude towards an injury prevention program. Results: The majority of players (86%) and staff members (91%) believe that injury prevention plays an important role on a professional level of playing and presume a moderate to extreme benefit of a regular injury prevention program in reducing the risk of injuries (78% of players and 91% of staff members, respectively). No significant relationships were observed between a positive attitude towards an injury prevention program and age (p=0.85), nationality (p=0.53), level of education (p=0.63), NLA experience (p=0.50) or occurrence of lower extremity injuries in the previous season (p=0.10). Conclusion: Players and staff members have considerable understanding about injury prevention and the use of a specific injury prevention program. Some of the players habits (e.g. correct exercise performance) were identified as barriers. Short-term program adherence was identified as a facilitator. Injury prevention programs can be implemented in players of different age, level of education and experience in NLA as well as in previously injured or non-injured players.